EFFECT OF FORMULATION FACTORS ON ORODISPERSIBLE TRIPTAN FORMULATIONS â€“ NOVEL APPROACH IN TREATMENT OF MIGRAINE - Sirisha, Yella; T E, Gopala Krishna Murthy; Rao, Avanapu Srinivasa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present research work is an attempt to determine the effect of various diluents and superdisintegrants on drug release of eletriptan orodispersible tablets and designs an optimized formulation using 22 factorial design. Further, evaluate the tablets for various pre-compression and post-compression parameters. Methods: The drug excipient compatibility study was conducted by infrared spectroscopy, differential scanning colorimetry and X-ray diffraction studies were conducted to test the purity of the drug. The tablets were formulated by direct compression method using spray dried lactose, mannitol, microcrystalline cellulose, starch as diluents and crospovidone, croscarmellose sodium, and sodium starch glycolate as superdisintegrants. The powder formulations were evaluated for pre-compression parameters such as bulk density, tapped density, Carr's Index, Hausner's ratio, and angle of repose. The tablets were evaluated for post-compression parameters such as the hardness, thickness, friability, weight variation, and disintegrating time in the oral cavity, in vitro drug release kinetics studies, and accelerated stability studies. The formulations were optimized by 22 factorial design. Results: The drug and excipients were compatible, and no interaction was found. The drug was pure, and all the pre-compression parameters were within Indian Pharmacopoeial Limits. Post-compression parameters were also within limits. The disintegration time was found to be 27 s for the formulation F29 containing Croscarmellose sodium (5%) and Mannitol as diluent, and in vitro drug release was found to be 99.67% in 30 min and follows first-order kinetics. This was also the optimized formulation by 22 factorial design with a p=0.013. Conclusion: The orodispersible tablets of eletriptan were successfully formulated, and the optimized formulation was determined that can be used in the treatment of migraine.